The Relationship between Physical Activity and Blood Pressure Status in Hypertensive Patients - Umi Sholihah Auliyatus Syifa Cantik; Fahrun Nur Rosyid (GLOBAL HEALTH SCIENCE GROUP, 2026)
Hypertension is a major global health problem with an increasing prevalence and a high risk of serious complications. Insufficient physical activity is recognized as a significant modifiable risk factor for elevated blood pressure. This study aims to identify the relationship between physical activity and blood pressure status in hypertensive patients in the working area of the Nguter Community Health Center, Sukoharjo Regency. This quantitative study employed a descriptive correlational design with a retrospective longitudinal approach. Sampling was conducted using purposive sampling based on specific criteria, resulting in 207 hypertensive respondents. Physical activity levels were assessed using the Global Physical Activity Questionnaire (GPAQ), which has been tested for validity and reliability. Blood pressure was measured using a sphymomanometer that had been calibrated by the Agency for the Security of Medical Devices and Facilities (BPAFK) in Surakarta. Data analysis involved univariate examination, bivariate testing with Spearman rank test, and odds ratio calculation. The majority of respondents had light physical activity (61.4%) and stage 2 hypertension (69.9%). The analysis showed a significant negative correlation between physical activity and blood pressure status in hypertensive patients (p < 0.001; r = -0.337). Respondents with light physical activity were 4.5 times more likely to have stage 2 hypertension than those with moderate and heavy physical activity (OR = 0.221; 95% CI: 0.118-0.415). In conclusion, respondents with light physical activity had a higher risk of developing stage 2 hypertension. Regular physical activity plays a crucial role in the prevention and control of hypertension. Education from health professionals and community motivation are necessary to enhance awareness of the benefits of regular physical activity.